(untitled) (Journal of Parents and Teachers, 2014)
FP centers of Jesuit Education work with families and students to see their formative experience from a perspective that goes beyond the specific circumstances of the episode of academic success or failure they are experiencing. In the view it answers the establishment of itineraries, which can start from the most basic stage, which is a PCPI, to the upper level of a training cycle